Classroom Assessment for EFL Learning to Speak at Junior high School - Luli Sari Yustina; Besral Besral; Hasnawati Hasnawati (AT-TA'LIM, 2021)
The present study investigated the current practice of EFL Classroom assessment focusing on speaking skills in Junior High School. Speaking Assessment is a tool used to evaluate students’ oral skills in the formal system by the English teachers. The investigation of classroom speaking assessment in this school was based on its effectiveness in light of alternative assessment tool and pedagogical values. By using ADDIE model, we constructed an oral assessment in accordance with the needs and levels of students as well as components on the oral assessment. There were five commons models such as Oral Interview, Role Play, Guessing Games, Story Telling and Oral Report that are communicative, relevant, continues, simple and various forms. These models can be used to assess students’ speaking skills regardless of time and place as its validity and practicality tests appeared to be high (93.75 and 87.5).  It can be concluded that these assessment models are applicable for teachers to assess students’ speaking skill. The paper further elaborates discussion on the utilizing of students’ ability, progress, and their learning process. In short, it is a high time for the teachers to apply these models in the classroom.